Assessment of selected psychosocial risk factors: stress, job burnout, and bullying in the case of medical staff as part of workplace ergonomics during the COVID-19 pandemic—A prospective pilot study - Rypicz, Łukasz; Witczak, Izabela; Gawłowski, Paweł; Salehi, Hugh Pierre; Kołcz, Anna (Frontiers in Public Health, 2023)
Background: The purpose of the pilot study conducted by the authors was to assess occupational risk in selected areas of psychosocial risk factors among health professions in a pilot study. Medical staff working in the healthcare sector experience stress, job burnout and bullying on a daily basis. Monitoring occupational risks in the above areas provides an opportunity to take appropriate preventive measures. Methods: The prospective online survey included 143 health care workers from various professional groups. 18 participants did not complete the survey, and the results of 125 participants were eventually included in the analysis. The study used health and safety questionnaires in the healthcare sector, which are not widely used as screening tools in Poland. Results: The following statistical methods were performed in the study: the Mann-Whitney test, Kruskal-Wallis test, Dunn's test. In addition, multivariate analysis was performed. The results obtained in the study indicate that the questionnaires used in the study can be widely used by employers or occupational medicine as screening tools. Conclusions: Our findings show that level of education attainment in healthcare is correlated with higher chance of experiencing stress and burnout. Among the surveyed professions, nurses reported a higher amount of stress and burnout. Paramedics reported the highest chance of being bullied at work. This can be explained by their nature of work which requires directly interacting with patients and their families. In addition, it should be noted that the tools used can be successfully applied in workplaces as elements of workplace ergonomics assessment in the context of cognitive ergonomics